2019
DOI: 10.1542/peds.2018-2065
|View full text |Cite
|
Sign up to set email alerts
|

A Treatment-Decision Score for HIV-Infected Children With Suspected Tuberculosis

Abstract: BACKGROUND: Diagnosis of tuberculosis should be improved in children infected with HIV to reduce mortality. We developed prediction scores to guide antituberculosis treatment decision in HIV-infected children with suspected tuberculosis. METHODS: HIV-infected children with suspected tuberculosis enrolled in Burkina Faso, Cambodia, Cameroon, and Vietnam (ANRS 12229 PAANTHER 01 Study), underwent clinical assessment, chest radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 31 publications
2
37
0
2
Order By: Relevance
“…As pointed out above, evidence on the utility of focused ultrasound for EPTB is reported from settings with moderate and high TB/HIV prevalence. 4,6,7 Recently the utility of lung ultrasound for PTB has also been reported and discussed for children and adults [8][9][10][11][12] ; however, more data are needed to better understand the diagnostic potential of lung ultrasound in discriminating PTB from other respiratory infections. The utility of systematic ultrasound investigation in settings with low TB/HIV-prevalence has not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As pointed out above, evidence on the utility of focused ultrasound for EPTB is reported from settings with moderate and high TB/HIV prevalence. 4,6,7 Recently the utility of lung ultrasound for PTB has also been reported and discussed for children and adults [8][9][10][11][12] ; however, more data are needed to better understand the diagnostic potential of lung ultrasound in discriminating PTB from other respiratory infections. The utility of systematic ultrasound investigation in settings with low TB/HIV-prevalence has not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal lymphadenopathy and focal splenic lesions (micro‐abscesses) correlated with HIV/TB co‐infection but were also prevalent in HIV‐negative children with PTB . Previous ultrasound studies in South African children with PTB had also reported that related abdominal lymphadenopathy and focal splenic lesions were frequent and a recent multi‐centre study from Asian and African countries suggested a diagnostic algorithm including ultrasonography for abdominal lymph nodes to guide antituberculosis treatment decision in HIV‐infected children with suspected TB . To date the potential diagnostic yield of systematically investigating children with presumptive TB for (concurrent) EPTB in addition to PTB has, however, not been studied in settings with low HIV/TB prevalence and ultrasound is commonly not systematically performed during TB work‐up.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the persistent challenges in laboratory-based diagnosis, it remains critically important to strengthen the capacity of front-line health care workers to clinically suspect and diagnose TB in children (Huynh et al, 2020). Pragmatic approaches providing evidence-based treatment decision support provides a way forward (Marcy et al, 2019). As a global community we will have to accept a degree of over-treatment if we want to close the case detection gap in children.…”
Section: Closing the Tb Case Detection Gapmentioning
confidence: 99%